(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2025)
This article presents the research journey based on the proposition of the object as a trigger for prior dramaturgy in animation theater. The project combines the disciplines of Animation Theater and Dramatic Writing from the Performing Arts program at the Federal University of Santa Catarina (UFSC), aiming at artistic and pedagogical experimentation. The initial result of the writing practice based on objects was promising, as it activated an available repertoire offered in the Animation Theater course, stimulated creativity, and allowed the characteristics of the object to indicate more apparent paths for composing the dramatic text, facilitating focus and defining the scope of scene creation.